Climate Variability, Child Labour and Schooling: Evidence on the Intensive and Extensive Margin - Jonathan Colmer (Fondazione Eni Enrico Mattei (FEEM), 2013)
How does future income uncertainty affect child labour and human capital accumulation? Using a unique panel dataset, we examine the effect of changes in climate variability on the allocation of time among child labour activities (the intensive margin) as well as participation in education and labour activities (the extensive margin). We find robust evidence that increased climate variability increases the number of hours spent on farming activities while reducing the number of hours spent on domestic chores, indicating a substitution of time across child labour activities. In addition, we find no evidence of climate variability on enrolment decisions or educational outcomes, suggesting that households may spread the burden of labour across children to minimize its impact on formal education.
Keywords: D13; O12; J13; J22; Q54; 330; Climate Variability; Child Labour; Schooling